The Constitutionality of Water Irrigation Policy in Morocco: Sustaining Agricultural Security Amid Climate Change - Ezzerouali, Souad; Banane, Mohamed Cheikh; Anaya, Hamid; Radouane El mountafia (Journal of Indonesian Constitutional Law, 2025)
This study aims to evaluate the effectiveness of current irrigation water policies in Morocco, examine the alignment of institutional governance with constitutional and environmental principles, and propose alternatives that promote sustainable and equitable water use.  This study contributes to the government's efforts to manage and prevent irrigation water crises, ensuring that agricultural water needs are adequately met, particularly in light of the increasingly severe impacts of climate change. This study employs a qualitative analytical methodology, drawing on a governance and constitutional rights-based framework, and reviews legal texts, public policy documents, parliamentary debates, and relevant national and international reports. The findings reveal gaps between legislative commitments and implementation practices, especially regarding coordination among institutions, prioritisation of agricultural uses, and responsiveness to climate stress. The study concludes with several recommendations, most notably: reinforcing integrated water governance frameworks, strengthening the monitoring and evaluation of irrigation programs, and enhancing the legal enforcement of the constitutional right to water in policy execution. This research contributes to the field by linking constitutional governance with climate-resilient water policy for agriculture.